LITERATURE REVIEW ON SOCIAL ECONOMIC LAW: INTEGRATION BETWEEN LEGAL DYNAMICS AND SOCIAL WELFARE - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This article explores the literature on social economy law, highlighting the importance of integration between legal and economic policy dynamics in achieving social welfare. Successful implementation of policies that are responsive to technological change and the global economy relies on the adoption of best practices, transparency and accountability. Public participation in policy oversight is also considered essential to ensure inclusive and sustainable welfare. Thus, the synergy between law and economy is crucial in addressing global challenges and creating a just and prosperous society.